Impact of ERK5 on the Hallmarks of Cancer - Stecca, Barbara (Int J Mol Sci, 2019)
Extracellular signal-regulated kinase 5 (ERK5) belongs to the mitogen-activated protein kinase (MAPK) family that consists of highly conserved enzymes expressed in all eukaryotic cells and elicits several biological responses, including cell survival, proliferation, migration, and differentiation. In recent years, accumulating lines of evidence point to a relevant role of ERK5 in the onset and progression of several types of cancer. In particular, it has been reported that ERK5 is a key signaling molecule involved in almost all the biological features of cancer cells so that its targeting is emerging as a promising strategy to suppress tumor growth and spreading. Based on that, in this review, we pinpoint the hallmark-specific role of ERK5 in cancer in order to identify biological features that will potentially benefit from ERK5 targeting.